A value-based approach to the adoption of cryptocurrencies - Fernando García-Monleón; Anett Erdmann; Ramón Arilla (Journal of Innovation & Knowledge (JIK), 2023)
The use of cryptocurrencies offers attractive business opportunities, in the context of financial services, smart contracts and token-based business models. The objective of this study is to provide a value-based understanding of what drives people to use cryptocurrencies for value exchange. Based on the users' perceived value of the technology, as logic of decision making, we explore the role of perceived financial value and the perceived emotional value in the intention to use the technology. The unified technology adoption theory provides the potential drivers of these value concepts, which are extended accounting for sustainability. Furthermore, to capture users' evolving experience with blockchain technologies, we propose the concept of the cryptocurrency knowledge path, capturing the scope and depth of users' knowledge on the applicability of cryptocurrencies, as potential influence on the value concepts in the decision to actively use cryptocurrencies. For the analysis, a structural model is set up and estimated using partial least square analysis (PLS-SEM). We identify a positive effect of both value concepts, financial and emotional value, on the intention to use cryptocurrencies. However, interestingly, we find that the emotional value assessment is fully mediated through the knowledge path. Furthermore, we find that environmental sustainability considerations are fully mediated through either of the two value concepts. These results provide guidance for a customer-centric, sustainable design and marketing of crypto-projects.
Keywords: O3; D9; G2; G4; C3; 650; Blockchain experience; Cryptocurrency; Perceived value; Sustainable investment; Technology adoption